Shifting Dynamics: Who Holds the Reins in Decision-Making With Artificial Intelligence Tools? Perspectives of Gen Z Pre-Service Teachers - Merzifonluoglu, Ayse; Gunes, Habibe (Wiley, 2025)
Artificial intelligence (AI) is significantly shaping education and currently influencing pre-service teachers' academic and professional journeys. To explore this influence, the present study examines 389 Generation Z pre-service teachers' attitudes towards AI and its impact on educational decision-making at two state universities, using an explanatory sequential mixed-methods research design. Quantitative data were collected through the General Attitudes to Artificial Intelligence Scale (GAAIS) and an AI decision-making survey. It was followed by qualitative data gathered via semi-structured interviews to enrich the statistical trends with deeper thematic insights. SPSS was used for quantitative data analysis while MAXQDA was employed for a systematic analysis of the qualitative data. The analysis revealed that female pre-service teachers held more positive attitudes towards AI, with higher levels of AI knowledge contributing to these attitudes. Negative attitudes, however, were independent of gender, academic discipline or AI familiarity. Findings also reveal that AI tools, particularly ChatGPT, are primarily used as advisors, and pre-service teachers often adapt AI's suggestions to their preferences. AI is predominantly preferred for assignments, reports, projects and presentations. In AI acceptance, time and effort savings, innovative suggestions and unbiased recommendations are stated as key factors. However, there are ongoing trust concerns highlighting the necessity of keeping final decisions under human control. Based on these findings, comprehensive AI training for teachers and students in higher education is suggested.
Keywords: AI trust and acceptance; artificial intelligence (AI); artificial intelligence in education (AIED); decision-making; ethical considerations in AI; human-AI collaboration; pre-service teachers